Moderate-to-Severe Depression Adversely Affects Lung Function in Chinese College Students - Guo, Liya; Cao, Jianhua; Cheng, Peng; Shi, Dongzhe; Cao, Bing; Yang, Guang; Liang, Siyu; Su, Nan; Yu, Miao; Zhang, Chaowei; Liang, Rui; Wang, Yaru; et al. (Frontiers in Psychology, 2020)
In middle-aged and older adults, it is well established that depression is related to an increased risk of chronic obstructive pulmonary disease (COPD) but the association between depressive symptoms and the decline in lung function among healthy adults is unclear. The aim of this study was to examine this association by measuring lung function and depression severity among Chinese college students. A cross-sectional study was conducted among 3891 participants aged between 16-23 years. Lung function was estimated by measuring the forced vital capacity (FVC) using a spirometer, and depression severity was evaluated using the 20-item Zung Self-rating Depression Scale (SDS), with an SDS score of ≥40 indicating mild to severe depression. After adjusting for potential confounders, the geometric means (95% confidence intervals) of the FVC levels for the normal, mildly depressed, and moderate-to-severely depressed groups were 3446.1 (3418.6, 3470.3), 3415.2 (3357.7, 3473.8), and 3351.0 (3271.5, 3432.3), respectively (P for trend: 0.031). This study showed that depressive symptoms were independently related to a decline in the lung function among Chinese college students. In future, it is important to explore the effect of depressive symptoms on lung function and its causality among healthy adults by prospective cohort or intervention study.